Hubungan Kemampuan Bersosialisasi Siswa Terhadap Hasil Prestasi Belajar Siswa Sekolah Dasar - Relis; Endah Marwanti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze and analyze in depth the students' social skills which are influenced by the learning outcomes of elementary school students. The method in this study uses a correlational method with a quantitative approach. The population in this study is students of SDN Yogyakarta and a sample of 30 people determined by purposive sampling technique in one of the elementary schools in Yogyakarta City. The instruments in this ability are in the form of a test of students' ability to socialize 5 questions and a scale of student learning achievement results as many as 24 statement scales. The results of this study concluded that there is a positive influence between the results of learning achievement and the socialization ability of elementary school students. This shows that the higher the student's learning achievement, the higher the student's socializing ability will be. Factors that affect the high and low learning outcomes of students include: (1) students with a social attitude are still shy about what they want to convey (2) students can have many ideas in socializing that they are facing. Meanwhile, students who are not well socialized will tend to have difficulty blending in with their friends, students only socialize with their classmates.